2015
DOI: 10.3109/13813455.2015.1068336
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of pomegranate extract against cisplatin toxicity in rat liver and kidney tissue

Abstract: In conclusion, these results demonstrate that the anti-oxidant pomegranate juice might have a protective effect against cisplatin-induced toxicity in rat kidney, but not in liver. Pomegranate juice could be beneficial as a dietary supplement in patients receiving chemotherapy medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Increasing the concentration of cisplatin is the most common strategy to offset cisplatin resistance. However, high-dose cisplatin may cause severe liver toxicity, which is the main side-effect of cisplatin therapy (36,37). In the present study we demonstrated that vandetanib was as effective as high-dose cisplatin in impairing cisplatin-resistant NB subcutaneous tumor growth in vivo.…”
Section: Discussionsupporting
confidence: 53%
“…Increasing the concentration of cisplatin is the most common strategy to offset cisplatin resistance. However, high-dose cisplatin may cause severe liver toxicity, which is the main side-effect of cisplatin therapy (36,37). In the present study we demonstrated that vandetanib was as effective as high-dose cisplatin in impairing cisplatin-resistant NB subcutaneous tumor growth in vivo.…”
Section: Discussionsupporting
confidence: 53%
“…Harm to liver cells can cause escape into the serum owing to autolytic breakdown or cellular necrosis [ 52 ]. There are also some earlier studies suggesting escalated serum ALT and AST levels related to increased ROS [ 53 , 54 ]. Enhanced levels of CRE and BUN can be attributed to retention of Cis in terminal collecting duct, the distal nephron of kidneys.…”
Section: Discussionmentioning
confidence: 93%
“…There are many studies indicating the relation between oxidative stress, MDA, and Cis-induced liver and kidney toxicity [ 49 , 50 , 53 ]. MDA is one of the basic indicators of oxidative harm and has been considered to take a significant part in the toxicity of several xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dysregulation of MAPK signaling pathways has been demonstrated in acute and chronic kidney disease induced by cisplatin [7]. Compounds isolated from natural sources, such as Artemisia asiatica , pomegranate, and Chrysanthemum indicum , have been shown to reduce the nephrotoxicity due to cisplatin [8], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%